MORPHOSYNTACTIC ABILITIES IN CHILD WITH INTELETUAL DISABILITIES: CASE STUDY - Kumaralalitya Wisnu Pambayun; Agus Subiyanto (Elite Laboratory English Department Universitas Bangka Belitung, Indonesia, 2023)
The case study in this study used a subject named KH with mild intellectual disability which was seen through the subject's morphosyntactic abilities. In this study using the assessment method to determine the ability of KH in morphology and syntax when speaking in everyday life. The researcher asked KH to tell KH's daily activities and was asked to retell from the available pictures. From this research it can be concluded that KH in making sentences is capable and in accordance with sentence elements such as Subj-Pred-Obj-Ket-Conj. But in terms of morphological abilities, KH more often uses Pred with basic words in the sentences that are spoken than with affixed verbs. So that in that case it can cause confusion of meaning